2014
DOI: 10.1158/1940-6207.capr-14-0167
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive Protein and Risk of Colorectal Adenomas or Serrated Polyps: A Prospective Study

Abstract: Serum C-reactive protein (CRP) is a sensitive marker of systemic inflammation. Since there is a well-recognized relationship between local inflammation and colorectal cancer, we aimed to evaluate whether serum CRP levels were associated with the occurrence of colorectal adenomas and serrated polyps using data from a large adenoma prevention trial. 930 participants with a history of colorectal adenomas were enrolled in a randomized trial of calcium supplementation (1200 mg/day) for the prevention of colorectal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…C‐reactive protein is an inflammatory cytokine that has been positively associated with colorectal cancer risk in prospective studies, including the CLUE II cohort . However, research on CRP serum levels and adenomas has produced conflicting results and we found no association of serum CRP and adenomas in CLUE II . We also previously reported no association between circulating CRP and the level of inflammation in normal colonic tissue measured concurrently from individuals undergoing routine screening colonoscopy .…”
Section: Discussioncontrasting
confidence: 63%
“…C‐reactive protein is an inflammatory cytokine that has been positively associated with colorectal cancer risk in prospective studies, including the CLUE II cohort . However, research on CRP serum levels and adenomas has produced conflicting results and we found no association of serum CRP and adenomas in CLUE II . We also previously reported no association between circulating CRP and the level of inflammation in normal colonic tissue measured concurrently from individuals undergoing routine screening colonoscopy .…”
Section: Discussioncontrasting
confidence: 63%
“…Positive associations between CRP and adenoma have not been consistently observed in previous studies. 20 21 22 23 In a small case-control study, serum CRP was not associated with increased risk of colorectal adenoma; however, that study was limited, as only 135 adenoma cases were analyzed. 23 In a case-control study from Korea, serum CRP was not significantly different between normal and adenoma groups.…”
Section: Discussionmentioning
confidence: 99%
“… 15 16 19 A recent meta-analysis found a positive association between CRP level and CRC risk. 14 Due to the inconsistencies in previous results, 17 20 21 22 26 27 28 little was conclusively known about the relationship between CRP and colorectal adenoma. In a Japanese case-control study, Otake et al 26 reported a positive association between CRP and prevalence of large adenomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research phase clinical studies support that Galectin-3 ligand is elevated in colorectal cancers and that its binding partner galectin-3 is also increased in cancers 14,46 hs-CRP Inflammation is an early hallmark in cancer development, and indication is that CRP measurement may be helpful in assessment for patient risk for having screening relevant findings [47][48][49][50] Ferritin Ferritin, like CRP, is considered an acute phase reactant, with levels increasing in various clinical conditions including infections and cancers 18,48 Tumor Markers and Signatures well as age and gender identifying the model with the highest likelihood score. 29 This model was then used for the secondary endpoints.…”
Section: Galectin-3mentioning
confidence: 99%